Strong towns : a bottom-up revolution to rebuild American prosperity - Marohn, Charles L., Jr (John Wiley & Sons, Inc., 2020)
"American cities of all sizes financially struggle to do basic things: maintain streets, keep public safety workers employed, pay pensions, etc. The conventional response to these struggles is: more growth. If a city can induce more development, more construction, and more infrastructure, then it can grow its way to prosperity. Yet, what if the American approach to growth is the problem? What if the wealth generated by all that new investment isn't enough to support the infrastructure? That is the core premise of Strong Towns, a movement to change the way cities approach growth and development. While modern city development creates a short-term illusion of prosperity, it results in more long-term obligations than the community can handle. The Strong Towns response is a revolution in how we assemble the places we life. By shifting focus from state and federal growth initiatives towards the basic, day-to-day needs of residents, communities of all sizes can make low risk investments that simultaneously strengthen the community financially while improving quality of life"--